IMPROVEMENT OF KNOWLEDGE OF HIJAIYAH LETTERS THROUGH THE MEDIA OF HIJAIYAH LETTERS CARD - Makrufatul Hidayah; Ahmad Majidun (Institut Agama Islam Syubbanul Wathon Magelang, 2022)
This community service is motivated by children who do not understand hijaiyah letters, especially children who are still at an early age. One of the reasons is the need for more educators with many children and different classes. This method that small children cannot understand makes early childhood, even children who have entered elementary school, not yet understand and have yet even to memorize the letter hijaiyah. The researcher here tries to use iqro` as a first step to find out how well the children of Madrasah Diniyah Al Abror understand the hijaiyah letter. With iqro` children are still unable to read letters. Then the researchers used hijaiyah cards as an introduction to hijaiyah letters. Because hijaiyah letters attract children's interest in memorizing hijaiyah letters, children can participate in memorizing hijaiyah letters well. The method used to attract children's attention is to use games that can make children not easily bored memorizing. In addition, researchers also invited children to memorize hijaiyah letters by using simple songs.